The psychological impact of the rise in media reporting of sexual violence after COVID-19 pandemic on Pakistani women’s mental health - Ghazal, Pasha; Akbar, Shehzeen (Social Psychiatry and Psychiatric Epidemiology, 2024)
Purpose Pandemics usually have inequitable effects on the most vulnerable groups of society. Since the start of COVID-19, there has been a horrifying upsurge in cases of sexual and gender-based violence against women, globally. Consequently, frequent breaking news of sexual violence in media aggravated mental distress and worry among women. In this cross-sectional study, we investigated the impact of the rise in active circulation of news of sexual violence on the mental health of working women and students using the validated DASS-21 questionnaire. Methods A total of 303 women with diverse socio-demographic backgrounds participated in the study. We performed a chi-square test to analyze the association of increase in media reporting with DASS-21total and sub-categories scores. Multivariate linear regression was performed on propensity score-matched subjects to identify psychosocial predictors of mental distress. Results Increased self-reported worries in response to rise in media reports of sexual violence was found to be significant predictor of mental distress ( p < 0.002). Moreover, highly significant correlation between the increase in media reports and scores of depression, anxiety, and stress was observed ( p < 0.001). Conclusions The rise in media reporting of sexual violence in the after math of COVID-19 was found to have a significant psychological impact on the mental health of Pakistani women. This is the first study of its kind on the subject and provides fundamental findings for shaping policy change on responsible media reporting of sexual violence.